Hip Abduction Strength: Relationship to Trunk and Lower Extremity Motion During A Single-Leg Step-Down Task in Professional Baseball Players - M. Christopher Zipser; Hillary A Plummer; Nathan Kindstrand; Johnathan C Sum; Bernard Li; Lori A Michener (International Journal of Sports Physical Therapy)
# Background